Existence of Solutions for a Class of Kirchhoff-Type Equation via Young Measures. (21st May 2021) - Azroul, Elhoussine; Balaadich, Farah
Abstract: In this article, our aim is to obtain weak solutions for a class of Kirchhoff-type problems − M ( ∫ Ω A ( x, ∇ u ) d x ) div a ( x, ∇ u ) = f ( x, u ) in Ω, by using the theory of Young measures.